Factors Affecting Decision Making Behavior on Purchasing through E-Commerce of the People Living in Municipal Area, Mahasarakham Province - My, Hoang Thi; Sansom, Asst. Prof. Dr. Kemika; Chareonchai, Dr. Kittichai (Journal for Developing the Social and Community, 2019)
The objective of this research was to study the factors of online marketing mix affecting decision making behavior on purchasing through E-commerce and study the individual factors affecting decision making behavior on purchasing through E-commerce. From the analysis level of decision making it was found that the factors of online marketing mix are vital elements to operation a business online and the factors the stimulus decision making behavior of consumers as well. Wherewith consumers value every aspect at a high level by focusing on the place the most. Individual factors are factor that determine consumer behavior and is important in deciding whether to buy or not. Which consumers give overall importance at a high level by focusing on the attitude as much as possible and the results from the hypothesis testing found that the factors of online marketing mix and individual factors have a positive impact on the decision making behavior on purchasing through E - commerce of the people living in municipal Area, Mahasarakham Province. The research results was found that the factors of online marketing mix was Promotion, personalization, product, place, price and Individual factors was attitudes, trust affecting decision making behavior on purchasing through E - commerce, whereas factors of privacy have no affecting decision making behavior on purchasing through E-commerce of the people living in municipal Area, Mahasarakham Province.